Pengaruh Penerapan Good Corporate Governance dan Keberadaan Awig-Awig terhadap Kinerja Keuangan Lembaga Perkreditan Desa dengan Budaya Tri Hita Karana sebagai Variabel Moderasi - Jayantari, Putu Rima; Gorda, A.A. Ngurah Eddy Supriyadinata (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aimed to determine the influence of the implementation Good Corporate Governance and the existence of awig - awig on the financial performance of LPD with Tri Hita Karana culture as a moderated variable in the LPD in Mengwi sub-district. This study used a saturated sampling method and the data analysis technique used was Moderated Regression Analysis. T test results show that:1) Good Corporate Governance had a positive effect on Financial Performance; 2) The existence of Awig-awig had a positive effect on financial performance; 3) Tri Hita Karana Culture strengthens the influence of Good Corporate Governance on Financial Performance; 4) Tri Hita Karana's culture strengthens the influence of Awig-awig's Existence on Financial Performance.